Hediste diversicolor as a biological model for the study of the effects of nanoplastics - Silva, Marta Sofia Salvador Lopes da (2020)
Plastics became ubiquitous in marine environments and have been considered emerging contaminants of concern. Oceans and coastal environments concentrate plastic debris, which ultimately can sediment due to factors like biofouling processes. Nonetheless, only a limited number of studies have focused on invertebrates and nanoplastics (defined as particles of sizes smaller than 100 nm). Polychaetas are important benthic species that influence the biogeochemical cycle of nutrients and the availability of contaminants. They are key species in estuarine ecosystems, usually living in the sediments and being exposed to the contaminants present in the sediments and in the pore water. Considering the need for more information on the potential environmental consequences of nanoplastics and sensitivity and ecological relevance of Hediste diversicolor, this dissertation aimed to study the effects of nanoplastics on this species. Thus, the first task of this dissertation included a review of the literature focusing on the effects of pharmaceutical drugs, nanoparticles and plastics in H. diversicolor. After the literature review, the behavior and distribution of polystyrene nanoplastics (100 nm) (PS NPs) in seawater were assessed, as well as the effects on behavior, biochemical endpoints and regenerative capacity of the polychaeta H. diversicolor. Overall, the results demonstrated that PS NPs tended to aggregate/agglomerate and sediment in seawater making them more available to benthic organisms. H. diversicolor, exposed to PS NPs for 28 days via water, presented altered burrowing activity and biochemical endpoints, like cholinesterase (ChE) activity, mainly at lowest concentrations tested (0.005-0.5 mg/L). The detected alterations in behavior may have ecological consequences affecting nutrient cycling as well as have an impact on intra-sediment fauna. Oxidative damage like protein carbonylation was observed, demonstrating a higher sensitivity to PS NPs contamination than lipid peroxidation (LPO). Exposure to PS NPs also demonstrated that these particles compromise the regenerative capacity of H. diversicolor, mainly at higher concentrations (0.05-5 mg/L), where organisms regenerated less than control (between 23.8 and 28.9%). This effect may have impacts on population maintenance, since Organisms may prioritize regeneration over reproduction. Overall, the data obtained in this dissertation demonstrates that NPs may have a considerable impact on benthic organisms, emphasizing the need of further studies aiming to assess the potential effects and mechanisms of action of these particles in organisms at the base of food webs. The consequences of the presence of NPs may be considerably higher considering that these particles have been demonstrated to play a “trojan horse” effect promoting the incorporation of other environmental pollutants.